Collective Management of Natural Resources Based on Traditional Values in West Sumatera Indonesia - Sukma Utami, Ami; Oue, Hiroki (European Journal of Sustainable Development, 2021)
Collective management of natural resources based on local values and practices is essential for sustainable management of natural resources. This study reassessed the traditional collective management of natural resources related to agriculture in West Sumatera. Descriptive analysis was used to evaluate the Adat (custom) of Minangkabau in natural resources management. The results showed that forest and stream are essential to the community as they provide ecosystem services such as clean air and the guidance of community culture. In managing the natural resources, Adat and religious values are fundamental principles. Based on these values, the traditional practices to protect and utilize nature are Rimbo Larangan (prohibited forest) and Lubuak Larangan (prohibited river). Additionally, Parak (agroforestry), Tanah Ulayat (communal land for agriculture), and Alek Banda (harvest ceremony) are the collective management of natural resources related to agriculture. These practices are based on fundamental principles, which are; (1) collective knowledge of Adat; (2) role of indigenous leader; and (3) Mufakat (consensus) in the decision-making process. Based on these traditional practices, the community can utilize the natural resources fairly and sustain the nature. Thus, this study suggests that the Adat Minangkabau in natural resource management needs to be conserved by utilizing traditional indigenous concepts.